2007
DOI: 10.1111/j.1744-7917.2007.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid compositions of predator Piocoris luridus (Heteroptera: Lygaeidae) and its host Monosteria unicostata (Heteroptera: Tingidae) reared on almond

Abstract: Fatty acid analysis of P. luridus and its host 461Abstract The changes in fatty acid compositions during nutritional interaction among almond Amygdalus communis Linnaeus (Rosales: Rosaceae) (host plant), lacebug Monosteria unicostata (Mulsant and Rey) (Heteroptera: Tingidae) and its predator Piocoris luridus Fieber (Heteroptera: Lygaeidae) were determined by gas chromatography and gas chromatography-mass spectrometry analyses. The fatty acid profiles of phospholipids and triacylglycerols were substantially dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Despite the general observations that long‐chain PUFAs are absent in terrestrial insects (Stanley‐Samuelson et al ., ; Rumpold & Schluter, ; Sanchez‐Muros, Barroso & Manzano‐Agugliaro, ), EPA has been reported to constitute significant proportions of total phospholipids in some terrestrial Heteroptera such as Monosteria unicostata (Tingidae) and its predator Piocoris luridus (Lygaeidae) as well as the pentatomid Eysarcoris inconspicuus (Cakmak, Bashan & Bolu, ; Cakmak, ). We studied the total lipid fraction, which contains less PUFA than the phospholipid fraction, but the proportions of EPA in waterbugs that we studied were higher than or at least similar to those in the phospholipids of the terrestrial Heteroptera.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the general observations that long‐chain PUFAs are absent in terrestrial insects (Stanley‐Samuelson et al ., ; Rumpold & Schluter, ; Sanchez‐Muros, Barroso & Manzano‐Agugliaro, ), EPA has been reported to constitute significant proportions of total phospholipids in some terrestrial Heteroptera such as Monosteria unicostata (Tingidae) and its predator Piocoris luridus (Lygaeidae) as well as the pentatomid Eysarcoris inconspicuus (Cakmak, Bashan & Bolu, ; Cakmak, ). We studied the total lipid fraction, which contains less PUFA than the phospholipid fraction, but the proportions of EPA in waterbugs that we studied were higher than or at least similar to those in the phospholipids of the terrestrial Heteroptera.…”
Section: Discussionmentioning
confidence: 99%
“…Later, numerous studies have confirmed that aquatic insects, including mosquitoes, accumulate high levels of C20 PUFA, in contrast to terrestrial species (Dadd et al, 1987;Howard & Stanley-Samuelson, 1996;Yang et al, 2006;Makhutova et al, 2011). However, some carnivorous terrestrial insects also may accumulate high proportions of C20 PUFAs (Cakmak et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The data presented here indicate that the quantitatively major FA associated with PLs and TGs prepared from A. rostrata include C16:0, C18:0, C18:1, C18:2n-6, and C18:3n-3, as described for many other Heteroptera and most other insect orders (Fast, 1970;Cakmak et al, 2005Cakmak et al, , 2007. Although these components are common to most insects, the FA composition of PL and TG from various heteropteran species are considerably variable.…”
Section: Discussionmentioning
confidence: 80%
“…The dipteran pattern of high C16:1 was also seen in four heteropterans; Blissus leucopterus leucopterus (Say) (Hemiptera: Lygaeidae), Blissus iowensis Andre (Spike et al, 1991), Eurygaster maura (Linnaeus) (Heteroptera: Scutelleridae) (Kilincer et al, 1987), and Eurygaster integriceps Puton (Bashan et al, 2002). However, proportion of C16:1 are low in most Heteroptera (Thompson, 1973;Bashan and Cakmak, 2005;Cakmak et al, 2005;Cakmak et al, 2007). Presumably, these patterns are somehow adaptive, although the manner in which this occurs is unknown.…”
mentioning
confidence: 91%